Maternal psychological distress in the early postpartum period during COVID-19 pandemic: a pilot study - Yao-Sheng Wang; Wen-Hsin Cheng; I-Lun Chen; Hsin-Chun Huang (BMC, 2022)
Abstract Background The coronavirus disease 2019 infection (COVID-19) pandemic is a new global outbreak disease. According to the Taiwan Centers for Diseases Control statement, hospitals had to change their corresponding measures to prevent the spread of COVID-19. The frequency of parental visits to the special care nursery was reduced from three times to once daily. Visiting was not permitted from April 4 to May 10, 2020, and rooming-in with healthy neonates was discontinued, which could increase maternal postpartum distress. Therefore, this study was conducted to determine whether COVID-19 prevention increased maternal psychological distress. Methods This prospective study used convenience sampling to enroll healthy mothers who had just delivered via normal spontaneous delivery. Based on the neonates' status and visiting times, mothers were grouped into no-rooming-in, rooming-in, no-visiting, and one-visit/day groups. Mothers' baseline characteristics were compared using the Chi-square or Fisher's exact test and t-test. Salivary cortisol levels and scores of Chinese versions of the Perceived Stress Scale (PSS) and State-Trait Anxiety Inventory were evaluated on postpartum days 1 and 3 and analyzed by one-way analysis of variance and a paired t-test. Results There were 16, 58, 28, and 47 women categorized as no-rooming-in, rooming-in, no-visit, and one-visit/day groups, respectively. No significant differences were found between groups in mothers' baseline characteristics and postpartum salivary cortisol levels. The PSS on day 3 was significantly higher than on day 1 in every group (p < 0.001). The PSS increasing trend in the no-rooming-in group was significantly greater than that in the no-visit group (p = 0.02) and significantly greater in the rooming-in group than that in the one-visit/day group (p = 0.001). Conclusion Postpartum stress increased for all mothers and was an even more significant response to the COVID-19 pandemic than the stress associated with neonates' hospitalization.